2014
DOI: 10.1080/10942912.2012.749410
|View full text |Cite
|
Sign up to set email alerts
|

Degradation Kinetics of Jujuboside a by Rat Intestinal Flora and Identification of the Metabolites by HPLC-Ms/Ms

Abstract: Jujuboside A (JuA) is a representative saponin with significant sedative and hypnotic effects.Up to now, there were many arguments on its metabolic mechanism. In this study, a high performance liquid chromatography-tandem mass spectrometry (MS/MS) method was developed for investigating the degradation characteristics of JuA incubated with rat feces. With the method, the degradation kinetics of JuA was studied. The results showed JuA decomposed rapidly. It could decompose nearly 100% in only 4-6 h. The degradat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 26 publications
3
12
0
Order By: Relevance
“…Therefore, the bacosides are likely to undergo transformation in vivo to remove the sugar units as well as other biotransformations, that result in metabolites that may mediate the memory enhancing and cognitive activities. This is consistent with other neuropharmacologically active plants such as ginseng [ 12 ], Ginkgo biloba [ 49 ] and jujube (red date) [ 13 , 14 ], where their respective active constituents are formed via the metabolism of the parent compounds in vivo .…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Therefore, the bacosides are likely to undergo transformation in vivo to remove the sugar units as well as other biotransformations, that result in metabolites that may mediate the memory enhancing and cognitive activities. This is consistent with other neuropharmacologically active plants such as ginseng [ 12 ], Ginkgo biloba [ 49 ] and jujube (red date) [ 13 , 14 ], where their respective active constituents are formed via the metabolism of the parent compounds in vivo .…”
Section: Discussionsupporting
confidence: 86%
“…CBG is capable of hydrolyzing a broad range of glycosides including glucosides, galactosides, xylosides, arabinosides, and fucosides [ 54 ]. Besides this, glycosides that are not substrates for LPH, CBG and SGLT-1, will be transported towards the colon where they may be hydrolyzed by colonic bacteria to release the aglycones, which can then be absorbed into the systemic circulation via passive uptake [ 12 , 14 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A controversial hypothesis is the induced enteritis due to saponins and/ or to the gut microbiota; as it is well known that gut bacteria promote intestinal inflammation (e.g., Ding et al, 2010;Peek & Blaser, 1996;Yan, Yang, & Ji, 2009). However, to the author's knowledge, no information is available on the effect of soy saponins on gut microbiota in salmonids, in contrast to that reported for other sources of saponins on gut microbiota of endothermic animals (Chen, Tai, & Hsiao, 2015;Gong, Xiao, Wang, & Yang, 2014;Juan, Zhang, Wang, An, & Wang, 2013;Wan et al, 2013;Zhang, Xie, Zhang, & Zhang, 2014). However, it is revealed that SBMIE lead to modulation of the Atlantic salmon gut microbiota (Reveco et al, 2014) and bacterial DNA in rainbow trout plasma (Mosberian-Tanha et al, 2016), as well as oxazole-induced enteritis in zebrafish modulate the gut microbiota (Brugman et al, 2009).…”
Section: Interactions Between the Immune Response And Gut Microbiotmentioning
confidence: 99%
“…Metabolomic studies have been applied in food science with the aim to determine geographical origin and particular organoleptic characteristics of varied products, such as potato, watermelon, wheat, rice, and green tea, [8] as well as the characterization and quality evaluation of special species. [9][10][11][12] Metabolomics analysis of clinically relevant bacteria can also be performed in combination with HPLC or gas chromatography-mass spectrometry (GC-MS). [13,14] Ye et al [15] also performed a nutrients and quality assessment of crab paste by 1 HNMR spectroscopy and multivariate data analysis.…”
Section: Introductionmentioning
confidence: 99%